Developing enterprise activities near a young national park: the views of municipal decision-makers and entrepreneurs adjacent to Repovesi National Park - Selby, Ashley; Petäjistö, Leena (Finnish Forest Research Institute, 2009)
The paper examines the tourism-oriented enterprise development measures preferred by entrepreneurs and decision-makers in the area adjacent to Repovesi National Park. The starting point is that visitors to Repovesi National Park spend considerably less money per visit than visitors to e.g. Linnansaari and Seitseminen national parks. Visitors to Repovesi are also less satisfied with the provision of (enterprise-based) services. The large volume of visitors to the national park should form a viable basis for tourism businesses.Tourism service enterprises are mostly very small enterprises that rarely have the resources for large investments or marketing. Thus, close cooperation is required between entrepreneurs and community leaders who decide on the allocation of development resources. Such co-operation may not always be forthcoming because local decision-makers may not consider the tourism industry sufficiently important. In this study, decision-makers tended to prefer solutions that involved various forms of funding. They also differentiated between direct support and Leader-based funding. They also differentiated between developing the business-support infrastructure and measures such as meetings, courses and other methods of information-dissemination. Entrepreneurs were less able or willing to delimit such specific groups of measures; for example, various forms of funding were generally considered together. Entrepreneurs were more likely to prefer practical, infrastructure support that would improve the preconditions for business (operating space, entrepreneurship incubators, etc.), as well as measures to assist the recognition of new business opportunities (workshops, meetings, visits to the national park, etc.).Decision-makers in the municipalities adjacent to Repovesi differed in their preferences for encouraging tourism-based development. In Mäntyharju, there was still a strong commitment to develop agriculture together with tourism. Other industrial developments were preferred to tourism. Decision-makers in Valkeala preferred the equal development of a number of segments of the economy. This was reflected in the preferred small business support measures. In Mäntyharju, more emphasis was placed on Leader-programme funding, whereas in Valkeala, there was a greater preference the developing the Leader-programme infrastructure, e.g. via cooperation. Fewer differences were found between entrepreneurs preferred measures at the municipal level. Most preferred measures to improve information and cooperation, followed by measures to assist access to funding and operating space and competence building. Entrepreneurs and decision-makers in Valkeala show more agreement on how to develop local tourism service enterprises than is the case in Mäntyharju, where there seems need to strengthen the dialogue between tourism entrepreneurs and decisions-makers.
Keywords: enterprise development; entrepreneurs; local decision-makers; Repovesi National Park; tourism